The Drosophila islet gene governs axon pathfinding and neurotransmitter identity. - Thor, S.; Thomas, J.B. (Neuron, 1997)
We have isolated the Drosophila homolog of the vertebrate islet-1 and islet-2 genes, two members of the LIM homeodomain family implicated in the transcriptional control of motor neuronal differentiation. Similar to vertebrates, Drosophila islet is expressed in a discrete subset of embryonic motor neurons and interneurons that includes the dopaminergic and serotonergic cells of the ventral nerve cord. In contrast to mouse where mutation of islet-1 leads to loss of neurons due to programmed cell death, Drosophila islet is not required for neuron survival. Instead, loss of islet function causes defects in axon pathfinding and targeting plus loss of dopamine and serotonin synthesis. Ectopic expression of islet induces both specific alterations in pathfinding and changes in neurotransmitter identity. These findings indicate that islet coordinately controls two distinct aspects of neuronal identity.